Current model predictive control for three-phase active power filter using cascaded h-bridge multilevel converter - Abdelkader Yousfi; Youcef Bot; Fayçal Mehedi; Abdelkader Chaker (Institute of Advanced Engineering and Science, 2021)
Different technologies in particular in the medium and high-power conversion were implemented and taken into consideration in the last few years. These inverter topologies have been demonstrated to ensure the generation of high-quality voltage waveforms based on power half-conductor switches, which operate on the fundamental frequency. The multilevel inverter H-bridge is a promising alternative among the available multi-level inverter topologies. A predictional current control algorithm for multi-level converters and use on a three-phase cascaded inverter H-bridge. This article reports on a comparison of two check methods associated with a shunt active power filter based on the cascaded inverter of the three- Level type. The first approach is the traditional PI control unit and the second is the predictive current control unit. The reference current for the shunt active power filter is provided by the p-q control strategy for reactive power compensation and current harmonics. The cascade-type three-level inverter has more advantages over a two-leaved inverter; the simulation output of APF is checked by MATLAB/Simulink. The predictive controlled the APF associated with the three-level inverter shows more performances and efficiency compared to the conventional control algorithms.